To Draft or Not to Draft? Efficiency, Generational Incidence, and Political Economy of Military Conscription - Panu Poutvaara; Andreas Wagener (Institute for the Study of Labor (IZA), 2005)
We study the efficiency and distributional consequences of establishing and abolishing the draft in a dynamic model with overlapping generations, taking into account endogenous human capital formation as well as government budget constraints. The introduction of the draft initially benefits the older generation while harming the young and all future generations. Its Pareto-improving abolition requires levying age-dependent taxes on the young. These being infeasible, abolition of the draft would harm the old. The intergenerational incidence of the gains and losses from its introduction and abolition helps to explain the political allure of the draft.
Keywords: D63; H20; H57; I21; 330; draft; conscription; education; intergenerational fairness; Wehrdienst; Bildungsinvestition; Overlapping Generations; Generationenbeziehungen; Gerechtigkeit; Public Choice; Theorie